Challenges in public procurement: An examination of legal implications of non compliance with procurement rules in selected institutions in Morogoro - Kweka, Eveline Elikira (Mzumbe University, 2023)
A Dissertation Submitted in Partial Fulfillment of the Requirement for the Award of Master of Laws [LLM- CL] of the Mzumbe University.